2017
DOI: 10.1097/mao.0000000000001371
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Stapes Surgery: A Comparison With Microscopic Surgery

Abstract: Air-bone gap closure and patient complications did not vary significantly between endoscopic and non-endoscopic groups in this study of 34 endoscopic procedures. There is a requirement for further studies with larger sample sizes and longer follow-up periods to fully gauge the safety and effectiveness of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 16 publications
4
30
2
Order By: Relevance
“…Overall, our results regarding preoperative to postoperative ABG changes are similar to those reported in previous studies addressing audiometric results after stapedotomy (12,13). The literature also indicates intraoperative complication rates of 0 to 6% and postoperative complication rates ranging from1 to 10%, similar to those reported in the present study (14,15).…”
Section: Discussionsupporting
confidence: 91%
“…Overall, our results regarding preoperative to postoperative ABG changes are similar to those reported in previous studies addressing audiometric results after stapedotomy (12,13). The literature also indicates intraoperative complication rates of 0 to 6% and postoperative complication rates ranging from1 to 10%, similar to those reported in the present study (14,15).…”
Section: Discussionsupporting
confidence: 91%
“…However, for tympanoplasty and stapes surgery, a comparison to available literature using GBI in microsurgery suggested similar or superior QoL measures amongst the cohort of patients from this study who underwent endoscopic ear surgery . The outcomes of endoscopic stapes surgery in our series of patients have been established by Sproat et al (2017), 80% of both endoscopic and non‐endoscopic groups had the average ABG closed to less than 10dB and there were no significant differences between the groups ( P −.940). The preliminary outcomes of TEES in our centre was also published recently and were comparable to results with microsurgery in the literature …”
Section: Discussionsupporting
confidence: 67%
“…Gulsen and Karatas 19 and Pradron and Preetam 20 reported the acceptable results with PTFE prosthesis. Sproat et al 26 and Iannella and Magliulo 27 reported the satisfactory surgical results of endoscopic stapes surgery using titanium prosthesis. Recently, Bianconi et al 7-18 reported the surgical results of 150 stapes surgery by TEES.…”
Section: Discussionmentioning
confidence: 99%